2020
DOI: 10.3390/cancers12082301
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Uterine Brachytherapy as Primary Treatment Option for Elderly Patients with Medically Inoperable Endometrial Cancer—A Single-Center Experience and Review of the Literature

Abstract: We aimed to gain more evidence regarding the feasibility, toxicity, and oncological outcome of primary brachytherapy in patients with medically inoperable endometrial cancer. Thirteen patients receiving primary brachytherapy ± external beam radiotherapy (EBRT) for endometrial cancer due to medical inoperability were identified. The Kaplan–Meier method was used to estimate overall survival (OS), progression-free survival (PFS), and local failure-free survival (LFFS). Univariate outcome analyses were performed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…For women with stage 1A grade 1 or 2 endometrioid endometrial cancer, brachytherapy alone has been shown to produce excellent results [14,21] and is an attractive alternative to a prolonged and potentially toxic course of combined treatment, especially if life expectancy is thought to be reduced. What is more, some institutions have developed protocols that utilise local anaesthetic/sedation only [22]. It is notable that all 5 deaths within 30 days of radiotherapy occurred in this group, 4/5 aged ≥80 years, suggesting poorer tolerance to pelvic radiotherapy in very elderly women.…”
Section: F I G U R E 1 Overall Survival (A-by Age Group B-stage C-tre...mentioning
confidence: 93%
“…For women with stage 1A grade 1 or 2 endometrioid endometrial cancer, brachytherapy alone has been shown to produce excellent results [14,21] and is an attractive alternative to a prolonged and potentially toxic course of combined treatment, especially if life expectancy is thought to be reduced. What is more, some institutions have developed protocols that utilise local anaesthetic/sedation only [22]. It is notable that all 5 deaths within 30 days of radiotherapy occurred in this group, 4/5 aged ≥80 years, suggesting poorer tolerance to pelvic radiotherapy in very elderly women.…”
Section: F I G U R E 1 Overall Survival (A-by Age Group B-stage C-tre...mentioning
confidence: 93%
“…In the 2D era, reported rates of local control were in the 75–85% range at 5 years,5 14 25 31–33 with severe late toxicity (grade 3 or 4) observed in up to 20% of patients 32 33. In the 3D era, excellent rates of local control have been reported of 85–90% at 2–3 years, with the majority of published series reporting no rates of severe late toxicity, and only a few series reporting a few isolated cases (<10%) of grade 3 or 4 events 14 23 25 27 28 34–42. Direct comparison of published series is limited due to heterogeneity of patient populations and treatment techniques.…”
Section: Outcomes Toxicity and Follow-upmentioning
confidence: 99%
“…Direct comparison of published series is limited due to heterogeneity of patient populations and treatment techniques. High-grade endometrioid disease, clear cell and serous papillary histology, as well as higher disease stage are factors that have been associated with higher rates of local failure and all-failure in multiple series 14 25 36 38 40. A summary of published experiences using 3D image-based treatment planning with either CT and/or MRI is shown in Table 3.…”
Section: Outcomes Toxicity and Follow-upmentioning
confidence: 99%
“…In the United States, 51,065 cases were diagnosed in 2020, with an expected increase up to 125,922 new cases in 2040 [1]. The main treatment is surgery ± radiotherapy ± chemotherapy, but about 10% of early-stage ECs are inoperable due to the body mass index (BMI), age-associated diseases, or anaesthetic contraindications [2][3][4]. Palliative approaches, such as hormone treatment, external beam irradiation (EBRT), and sometimes chemotherapy, have been described in the literature [3].…”
Section: Introductionmentioning
confidence: 99%